2015
DOI: 10.1596/1813-9450-7374
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional Cash Transfers in China: An Analysis of the Rural Minimum Living Standard Guarantee Program

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 8 publications
0
29
1
Order By: Relevance
“…Only one recent study used [2007][2008][2009] household data matched with administrative data to examine the anti-poverty effects of rural Dibao (Golan, Sicular, & Umapathi, 2014). The authors found that rural Dibao was unable to substantially reduce poverty, which was partly due to the large targeting errors.…”
Section: Welfare Participation In China: the Dibao Programmentioning
confidence: 99%
“…Only one recent study used [2007][2008][2009] household data matched with administrative data to examine the anti-poverty effects of rural Dibao (Golan, Sicular, & Umapathi, 2014). The authors found that rural Dibao was unable to substantially reduce poverty, which was partly due to the large targeting errors.…”
Section: Welfare Participation In China: the Dibao Programmentioning
confidence: 99%
“…Gao et al (2009) suggested that the dibao program lowers the poverty rate somewhat and reduces the poverty gap substantially for eligible participants; however, they too point out dibao's lack of coverage and delivery. More recently, Wu and Ramesh (2014) confirmed that dibao is an effective tool for reducing poverty, whereas Golan et al (2014) found income transfer under the rural dibao program's was sufficient for the recipients but the overall poverty reduction effect was limited due to coverage issues and targeting errors. In summary, this literature confirms the poverty reduction effect of China's dibao programs, although narrow coverage and targeting errors might have limited their effectiveness.…”
Section: Impacts Of Food Policy Of India and China On National And Glmentioning
confidence: 99%
“…While the poverty rate impressively fell from 14.8 per cent to 11.2 per cent between 2007 and 2009, Dibao decreased the annual poverty rate by less than half a percentage point (Golan et al . , ). Moreover, although expenditure on Dibao increased markedly from the equivalent of 17 per cent of the ex ante poverty gap to 62 per cent, Dibao reduced the poverty gap by just 2.3 per cent in 2007 and by 6.5 per cent in 2009 (Golan et al .…”
Section: Introductionmentioning
confidence: 97%